Isolation of highly polymorphic microsatellite loci for a species with a large genome size: Sharp-ribbed salamander (Pleurodeles waltl) - Van De Vliet, M. S. (2014)
Fourteen highly polymorphic microsatellite markers were developed and characterized for the sharp-ribbed salamander, Pleurodeles waltl. Isolating microsatellites with more than 12 single repeat type units was only successful for a tetranucleotide repeat (ATAG). Compared to microsatellite libraries constructed simultaneously for two anuran amphibian species, a greater number of primer pairs designed for P. waltl had to be discarded, due to consistent amplification problems. Low amplification success rate for P. waltl may be due to its larger genome size. Consequently, to avoid nonspecific binding and to increase amplification success, polymerase chain reaction programmes with touchdown cycles were used. For 14 microsatellite markers, amplification was successful and consistent with number of alleles and expected heterozygosity ranging from seven to 22 and from 0.79 to 0.94, respectively. All 14 microsatellite markers will be extremely useful for metapopulation studies of this unique amphibian species.